Strategi Inovatif Pemerintah dalam Meningkatkan Daya Saing Nasional dan Mencapai Keseimbangan Pasar yang Berkelanjutan - Hilya Hana Putri; Mohammad Kaka Syahwa Abbas; Siti Amalia Nurul Hadidah; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the context of globalization and digital transformation, national competitiveness is crucial for sustainable economic growth. This research aims to understand the complex relationship between government innovative strategies, national competitiveness, and market equilibrium. Through a literature review approach, this research highlights the important role of innovation in improving economic competitiveness, creating added value, and unlocking growth opportunities. The impact of fiscal policies, such as taxes and subsidies, on market equilibrium is also discussed in depth. In conclusion, effective integration between efforts to improve national competitiveness and achieve sustainable market equilibrium is key to inclusive and equitable economic growth.